Pengaruh Model Pembelajaran Think Pair Share Terhadap Kemampuan Komunikasi Matematis Siswa - Ika Marantika; Nurhanurawati Nurhanurawati; M Coesamin (JURNAL PENDIDIKAN MATEMATIKA UNIVERSITAS LAMPUNG, 2020)
The Influence of Think Pair Share Model Toward Student’s Mathematical Communication Skill. This research aimed to find out the influence of think pair share (TPS) model toward student’s mathematical communication skill. The population of this research was all students of grade 7th Junior High School state of Natar in academic year 2018/2019. Through purposive random sampling technique, students of class of VII-E and VII-F were chosen as the research sample. This research used the pretest-posttest control group design. The research data in the form of mathematical communication skill scores were obtained by the essay test on presentation data chapter. Based on the hyphotesis result of ????-test was known that TPS model was influence towards student’s mathematical communication skill. Keywords: influence, mathematical communication, think pair share